Acoustic monitoring system using wireless sensor networks - Muhammad Fahmi Firdaus Ismail. (2010)
In this technologically-driven century, wireless sensor networks have gained popularity over traditional sensors in several areas by providing better features and sensing capabilities. This project will focus on using WSN to sense sound. An acoustic monitoring system is developed to address the issue and limitations of large volume sampling. IRIS and MICAz sensor motes are used to realize the hardware requirements of the WSN and Labview software is used to perform the signal processing of the acquired data on the PC. Multi-hop capability of the mesh network is also implemented. A couple of limitations are encountered on the motes such as the limited sampling rate achievable on the mote and the size of the data to be acquired. In order to find out the various limitations of the mote, numerous tests are conducted and stable parameters are used in the final system. A comparison was made between the reconstructed audio and the original audio to highlight the key differences. A low level detection system is proposed. Problems encountered during the course of work are also highlighted and solutions are proposed. With all the required objectives met, the project has contributed to the development of an acoustic monitoring system.